(3acQI Yf ebOeI GdMGSHGJ (B= Introduction of Computerss - (3YRH, eMeO YRHs; (3eMehO, CfhQ YHO GdMejOs ((3GdbGgQIs (3GdOGQ GdeUQjI ddYdhes, 2008)
(3jJfGhd gPG GdcJGH GdehVhYGJ HTcd Yedi h HWQjbI LOjOI ddCNP HjO GdOGQS HCSQY hbJ eecf dJYde ebOeI GdMGSH h GMJQGag ai eOI JSYI CjGes
(3GdYGde ef MhdfG (B((3GdceHjhJQ(B)s
1 11
Keywords: Computer Science; (3GdMGSHGJ GdEdcJQhfjIs